Dampak Penegakan Hukum Perlindungan Terhadap Kesejahteraan Psikologis Perempuan dan Anak Korban Kekerasan - Nandhita, Aziza (Verdict: Journal of Law Science, 2023)
Law enforcement for the protection of women and children victims of violence, as stipulated in Law No. 23/2004 on the Elimination of Domestic Violence and Law No. 35/2014 on Child Protection, plays an important role in improving the psychological well-being of victims. This research aims to analyze the impact of law enforcement on the psychological well-being of women and children, with a focus on increasing a sense of security, emotional support, and courage to report. The method used is normative juridical with a legislative approach and document analysis. The results showed that law enforcement of protection has a positive impact, namely increasing the sense of security and psychological support of victims. However, its effectiveness is still constrained by structural barriers and social stigma. An increase in law enforcement that is more responsive and sustainable support is needed to maximize the psychological well-being of victims.